STUDI PEMANFAATAN PANDAN DURI (Pandanus tectorius) DI HUTAN TEMBAWANG OLEH MASYARAKAT DESA RIAM MENGELAI KECAMATAN BOYAN TANJUNG KABUPATEN KAPUAS HULU Study Using Thorns Pandan (Pandanus tectorius) in Tembawang Forest by Village Riam Mengelai in Boyan - Arista, Ardian; rizal, Fah; Dirhamsyah, M. (JURNAL HUTAN LESTARI, 2014)
Tembawang forest has a very large role for the life of the local community and society which are located around the forest area. Utilizing thorns pandan (Pandanus tectorius) is a forest conservation efforts in order to be able to enjoy the benefits of forests to the future. The method used is descriptive whereas for data collection used a structured interview using a questionnaire. The number of respondents in this study were 100 respondents. The results reveal that the level of utilization of pandanus thorns by society tends to be high. A total of 62 respondents (62%) had a utilization rate of thorns pandan in high tembawang woods, as many as 30 respondents (30%) had a utilization rate of thorns pandan tembawang forests are and as much as 8 resonden (8% ) has a utilization rate of thorns pandan in low tembawang forest. Keyword: Tembawang forest, thorns pandan